2020
DOI: 10.1111/ele.13454
|View full text |Cite
|
Sign up to set email alerts
|

Best be(e) on low fat: linking nutrient perception, regulation and fitness

Abstract: Preventing malnutrition through consuming nutritionally appropriate resources represents a challenge for foraging animals. This is due to often high variation in the nutritional quality of available resources. Foragers consequently need to evaluate different food sources. However, even the same food source can provide a plethora of nutritional and non-nutritional cues, which could serve for quality assessment. We show that bumblebees, Bombus terrestris, overcome this challenge by relying on lipids as nutrition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
94
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(116 citation statements)
references
References 77 publications
4
94
3
Order By: Relevance
“…They should, therefore, be able to also taste them in the artificial nectar diets used in our study, which is a prerequisite for regulation of their intake. The lack of amino acid regulation suggested by this study's findings does, however, agree with another study from our group, which also found no regulation of amino acid intake in B. terrestris foraging on pollen [50], suggesting that B. terrestris may instead regulate other nutrients, such as lipids [50] or carbohydrates.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…They should, therefore, be able to also taste them in the artificial nectar diets used in our study, which is a prerequisite for regulation of their intake. The lack of amino acid regulation suggested by this study's findings does, however, agree with another study from our group, which also found no regulation of amino acid intake in B. terrestris foraging on pollen [50], suggesting that B. terrestris may instead regulate other nutrients, such as lipids [50] or carbohydrates.…”
Section: Discussionsupporting
confidence: 88%
“…They may, however, have overeaten protein to obtain sufficient lipids or a suitable protein-lipid ratio, at least when fed the casein diet (according to the manufacturer, lipids are the main other component of casein), as indicated by the high protein consumption on this diet. In fact, lipids appear to be more strongly regulated by foraging bumble bees than carbohydrates [4,22,51] and may significantly affect colony [4,52,53] and also individual health [50]. Alternatively, the B. terrestris workers in our study may simply have ignored amino acids and may have focused on sugar intake only.…”
Section: Discussionmentioning
confidence: 94%
“…Also, while low concentrations of fat in pollen did not affect pollen consumption by bumblebees, increased concentrations (e.g. above 60 µg/mg pollen) strongly reduced pollen consumption [37,69]. These findings may be explained by the adverse effect of excessive amounts of fat on the bees' survival.…”
Section: Discussionmentioning
confidence: 87%
“…These findings may be explained by the adverse effect of excessive amounts of fat on the bees' survival. For example, survival of bumblebees was significantly lower when feeding on diets containing low P:F ratios and thus high fat concentrations than the survival of bumblebees feeding on diets containing higher P:F ratios [38,69]. Likewise, survival of honeybees (Apis mellifera) decreased with increasing dietary fat content [70].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation